2015
DOI: 10.1111/jcmm.12564
|View full text |Cite
|
Sign up to set email alerts
|

Acacetin inhibits expression of matrix metalloproteinases via a MAPK‐dependent mechanism in fibroblast‐like synoviocytes

Abstract: It is well known that rheumatoid arthritis (RA) is an autoimmune joint disease in which fibroblast-like synoviocytes (FLSs) play a pivotal role. In this study, we investigated the anti-arthritic properties of acacetin in FLSs. The expression of matrix metalloproteinase (MMP)-1, MMP-3 and MMP-13 were investigated by quantitative RT-PCR and western blot at gene and protein levels. At the same time, the phosphorylation of mitogen-activated protein kinases (MAPK) was investigated. The DNA-binding activity of NF-κB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The SuperScript TM III First-Strand Synthesis SuperMix for qRT-PCR Kit (Invitrogen) was used to reverse transcribe total RNA to complementary DNA (cDNA) following the manufacturer’s instructions. The amplification of MMPs, ADAMTS, and collagen II was performed using the Power SYBR® Green PCR Master Mix kit (Applied Biosystems, Foster City, CA, USA) under conditions of 95°C for 10 min, followed by 40 cycles at 95°C for 15 s and 60°C for 60 s [24]. To normalize expression, 18S rRNA was amplified as an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…The SuperScript TM III First-Strand Synthesis SuperMix for qRT-PCR Kit (Invitrogen) was used to reverse transcribe total RNA to complementary DNA (cDNA) following the manufacturer’s instructions. The amplification of MMPs, ADAMTS, and collagen II was performed using the Power SYBR® Green PCR Master Mix kit (Applied Biosystems, Foster City, CA, USA) under conditions of 95°C for 10 min, followed by 40 cycles at 95°C for 15 s and 60°C for 60 s [24]. To normalize expression, 18S rRNA was amplified as an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…Inflammation-related signaling pathways such as MAPK [including p38, jun N-terminal kinase (JNK), and extracellular regulated protein kinase 1/2 (ERK1/2)] and NF-kB are reported to be activated by advanced glycation end products (AGEs), which are considered to be major pathogenic metabolites in diabetic conditions (21,22). Growing evidence has demonstrated that activation of p38 and JNK signals may lead to MMP-13 expression enhancement (23)(24)(25), whereas NF-kB signaling was also reported to act as a crucial regulator in MMP-13 expression in NPCs (26). Meanwhile, our studies have found that autophagy may also be activated by AGEs and regulate MMP-13 in NPCs (27)(28)(29).These studies above suggest that MAPK, NF-kB signaling, and autophagy may regulate MMP-13 in IVDD, which may also be implicated in diabetic IVDD; however, the relationship between them and BRD4 in diabetic IVDD is still unknown.…”
mentioning
confidence: 99%
“…Both ERK and p38 MAPKs are activated during fibroblast contraction of stressed collagen matrices under isometric tension . The MAPK pathway may be a molecular mechanism for acacetin inhibition of MMPs in IL-1β-induced FLSs (Chen et al 2015). Based on these findings, we hypothesized that MAPK activation plays a critical role in transducing mechanical stimuli to elicit cellular responses.…”
Section: Discussionmentioning
confidence: 99%